The Impact of IL28B Gene Polymorphisms on Drug Responses - Nhan Phan, Tran; Thi Le Hang, Dp; Thi Thom, Vu; Doan Long, Dinh; Thi Hong Nhung, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4, 2021)
To achieve high therapeutic efficacy in the patient, information on pharmacokinetics, pharmacodynamics, and pharmacogenetics is required. With the development of science and technology, especially genetic sequencing technology, more and more research on pharmacogenomics has been conducted. The relationship between the genome and the response of a person to drugs is being explored to support personalized medicine, which shows efficacy in clinical treatment. In particular, the IL28B gene polymorphisms have been studied and shown to have impacts on drug responses in the treatment of many diseases, such as chronic hepatitis C, chronic hepatitis B, and myeloproliferative neoplasms. However, pharmacogenetic studies of the IL28B gene have not given exact recommendations for dose adjustment in treatment; they only show the impact tendency that individuals with an unfavorable genotype (usually the genotype of the mutant allele) show poor response to treatment compared to those with a favorable genotype. The frequency of mutant alleles varies among different ethnic groups and between different viral genotypes. Identifying and predicting the possibility of successful treatment helps both clinicians and patients make better choices of treatment decisions to optimize treatment possibilities, and reduce side effects and treatment costs. Keywords IL28B polymorphism, drug response, hepatitis C, hepatitis B, myeloproliferative disorders. References [1] V. M. Lauschke, M. I. Sundberg, The Importance of Patient - Specific Factors for Hepatic Drug Response and Toxicity, International Journal of Molecular Sciences, Vol. 17, No. 10, 2016, pp. 1714, https://doi.org/10.3390/ijms17101714. [2] E. Vesell et al., Genetic and Environmental Factors Affecting Drug Disposition in man, Clinical Pharmacology & Therapeutics, Vol. 22, No. 5, 1977, pp. 659-679, https://doi.org/10.1002/cpt1977225part2659. [3] M. J Sorich, R. A McKinnon, Personalized Medicine: Potential, Barriers and Contemporary Issues, Current Drug Metabolism, Vol. 13, No. 7, 2012, pp. 1000-1006, https://doi.org/10.2174/138920012802138615. [4] C. M. Lange, S. Zeuzem, IL28B Single Nucleotide Polymorphisms in the Treatment of Hepatitis C, Journal of Hepatology, Vol. 55, No. 3, 2011, pp. 692-701, https://doi.org/10.1016/j.jhep.2011.03.006. [5] Y. Luo, C. Jin, Z. Ling, X. Mou, Q. Zhang, C. Xiang, Association Study of IL28B: Rs12979860 and Rs8099917 Polymorphisms With SVR in Patients Infected with Chronic HCV Genotype 1 to PEG-INF/RBV Therapy using Systematic Meta-Analysis, Gene, Vol. 513, No. 2, 2013, pp. 292-296, https://doi.org/10.1016/j.gene.2012.10.030. [6] A. Muir et al., Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines for IFNL3 (IL28B) Genotype and PEG Interferon‐Α-Based Regimens, Clinical Pharmacology Therapeutics, Vol. 95, No. 2, 2014, pp. 141-146, https://doi.org/10.1038/clpt.2013.203. [7] The Pharmacogenomics Knowledgebase (PharmGKB), Drug Label Annotations, https://www.pharmgkb.org/gene/PA134952671/labelAnnotation/, 2020 (accessed on: April 10th, 2020). [8] A. Jazwinski, A. Muir, IL28B: Implications for Clinical Practice, Current Hepatitis Reports, Vol. 11, No. 1, 2012, pp. 15-22, https://doi.org/10.1007/s11901-011-0118-y. [9] Ensembl, Variant Table https://asia.ensembl.org/Homo_sapiens/Gene/Variation_Gene/Table?db=core;g=ENSG00000197110;r=19:39243553-39245129/, 2020 (accessed on: April 20th, 2020). [10] Ensembl, Explore This Variant, https://asia.ensembl.org/index.html/,02020 2020 (accessed on: April 20th, 2020). [11] Ministry of Health, Technical Guidelines on HCV Diagnosis and Treatment, Ministry of Health, Hanoi, 2016 (in Vietnamese). [12] A. J. V. D. Meer et al., Association between Sustained Virological Response and All-Cause Mortality Among Patients with Chronic Hepatitis C and Advanced Hepatic Fibrosis, Jama, Vol. 308, No. 24, 2012, pp. 2584-2593, https://doi.org/10.1001/jama.2012.144878. [13] J. J. Feld, J. H. Hoofnagle, Mechanism of Action of Interferon and Ribavirin in Treatment of Hepatitis C, Nature Genetics, Vol. 436, No. 7053, 2005, pp. 967-972, https://doi.org/10.1038/nature04082. [14] D. Ge et al., Genetic Variation in IL28B Predicts Hepatitis C Treatment-Induced Viral Clearance, Nature Genetics, Vol. 461, No. 7262, 2009, pp. 399-401, https://doi.org/10.1038/nature08309. [15] J. Fischer et al., Combined Effects of Different Interleukin‐28B Gene Variants on the Outcome of Dual Combination Therapy in Chronic Hepatitis C Virus Type 1 Infection, Hepatology, Vol. 55, No. 6, 2012, pp. 1700-1710, https://doi.org/10.1002/hep.25582. [16] E. Cariani et al., Interleukin 28B Polymorphisms As Predictors of Sustained Virological Response in Chronic Hepatitis C: Systematic Review and Meta-Analysis, The Pharmacogenomics Journal, Vol. 16, No. 1, 2016, pp. 18-29, https://doi.org/10.1038/tpj.2015.28. [17] Z. Jia, Y. Ding, S. Tian, J. Niu, J. Jiang, Test of IL28B Polymorphisms in Chronic Hepatitis C Patients Treated with Pegifn and Ribavirin Depends on HCV Genotypes: Results from A Meta-Analysis, Plos One, Vol. 7, No. 9, 2012, pp. e45698, https://doi.org/10.1371/journal.pone.0045698. [18] A. Moghaddam et al., IL28B Genetic Variation and Treatment Response in Patients with Hepatitis C Virus Genotype 3 Infection, Hepatology, Vol. 53, No. 3, 2011, pp. 746-754, https://doi.org/10.1002/hep.24154. [19] E. Mohammed et al., IFNL3 Polymorphisms Predict Response to Therapy in Chronic Hepatitis C Genotype 2/3 Infection, Journal of Hepatology, Vol. 61, No.2, 2014, pp. 235-241, https://doi.org/10.1016/j.jhep.2014.03.039. [20] T. M. Scherzer et al., Early Virologic Response and IL28B Polymorphisms in Patients with Chronic Hepatitis C Genotype 3 Treated with Peginterferon Alfa-2a and Ribavirin, Journal of Hepatology, Vol. 54, No. 5, 2011, pp. 866-871, https://doi.org/10.1016/j.jhep.2010.08.024. [21] J. Stenkvist, A. Sönnerborg, O. Weiland, HCV RNA Decline in Chronic HCV Genotype 2 and 3 During Standard of Care Treatment According to IL28B Polymorphism, Journal of Viral Hepatitis, Vol. 20, No. 3, 2013, pp. 193-199, https://doi.org/10.1111/j.1365-2893.2012.01645.x. [22] T. Asselah et al., IL28B Polymorphism is Associated with Treatment Response in Patients with Genotype 4 Chronic Hepatitis C, Journal of Hepatology, Vol. 56, No. 3, 2012, pp. 527-532, https://doi.org/10.1016/j.jhep.2011.09.008. [23] S. D. Nicola et al., Interleukin 28B Polymorphism Predicts Pegylated Interferon Plus Ribavirin Treatment Outcome in Chronic Hepatitis C Genotype 4, Hepatology, Vol. 55, No. 2, 2012, pp. 336-342, https://doi.org/10.1002/hep.24683. [24] M. Derbala et al., Interleukin-28 and Hepatitis C Virus Genotype-4: Treatment-Induced Clearance and Liver Fibrosis, World Journal of Gastroenterology, Vol. 18, No. 47, 2012, pp. 7003-7008, https://doi.org/10.3748/wjg.v18.i47.7003. [25] N. Antaki et al., IL28B Polymorphisms do not Predict Response to Therapy in Chronic Hepatitis C with HCV Genotype 5, Gut, Vol. 61, No. 11, 2012, pp. 1640-1641, http://dx.doi.org/10.1136/gutjnl-2012-302019. [26] S. Akkarathamrongsin et al., Early Viral Kinetics During Hepatitis C Virus Genotype 6 Treatment According to IL28B Polymorphisms, World Journal of Gastroenterology, Vol. 20, No. 30, 2014, pp. 10599-10605, https://doi.org/10.3748/wjg.v20.i30.10599. [27] C. Bucci et al., Favourable IL28B Polymorphisms Are Associated with A Marked Increase in Baseline Viral Load In Hepatitis C Virus Subtype 3a Infection and Do Not Predict A Sustained Virological Response After 24 Weeks of Therapy, Journal of General Virology, Vol. 94, No. 6, 2013, pp. 1259-1265, https://doi.org/10.1099/vir.0.051052-0. [28] M. L. Yu et al., Role of Interleukin‐28B Polymorphisms in the Treatment of Hepatitis C Virus Genotype 2 Infection in Asian Patients, Hepatology, Vol. 53, No. 1, 2011, pp. 7-13, https://doi.org/10.1002/hep.23976. [29] O. G. Shaker, N. A. Sadik, Polymorphisms in Interleukin‐10 and Interleukin‐28 B Genes in E Gyptian Patients with Chronic Hepatitis C Virus Genotype 4 and Their Effect on the Response to Pegylated Interferon/Ribavirin‐Therapy, Journal of Gastroenterology Hepatology, Vol. 27, No. 12, 2012, pp. 1842-1849, https://doi.org/10.1111/j.14401746.2012.07273.x. [30] W. K. Seto et al., Role of IL 28B and Inosine Triphosphatase Polymorphisms in the Treatment of Chronic Hepatitis C Virus Genotype 6 Infection, Journal of Viral Hepatitis, Vol. 20, No. 7, 2013, pp. 470-477, https://doi.org/10.1111/jvh.12047. [31] H. Zheng, M. Li, B. Chi, X. X. Wu, J. Wang, D. W. Liu, IL28B Rs12980275 Variant As A Predictor of Sustained Virologic Response to Pegylated-Interferon and Ribavirin in Chronic Hepatitis C Patients: A Systematic Review and Meta-Analysis, Clinics Research in Hepatology Gastroenterology, Vol. 39, No. 5, 2015, pp. 576-583, https://doi.org/10.1016/j.clinre.2015.01.009. [32] J. Chen et al., IL28B Genetic Variations Are Associated with High Sustained Virological Response (SVR) of Interferon-Α Plus Ribavirin Therapy in Taiwanese Chronic HCV Infection, Genes Immunity, Vol. 12, No. 4, 2011, pp. 300-309, https://doi.org/10.1038/gene.2011.1. [33] Y. Tanaka et al., Genome-Wide Association of IL28B with Response to Pegylated Interferon-Α and Ribavirin Therapy for Chronic Hepatitis C, Nature Genetics, Vol. 41, No. 10, 2009, pp. 1105-1109, https://doi.org/10.1038/ng.449. [34] [34] M. P. Vincent Soriano et al., Care Of Patients Coinfected with HIV and Hepatitis C Virus: 2007 Updated Recommendations from the HCV-HIV International Panel, Aids, Vol. 21, No. 9, 2007, pp. 1073-1089, https://doi.org/10.1097/QAD.0b013e3281084e4d. [35] C. S. Graham et al, Influence of Human Immunodeficiency Virus Infection on the Course of Hepatitis C Virus Infection: A Meta-Analysis, Clinical Infectious Diseases, Vol. 33, No. 4, 2001, pp. 562-569, https://doi.org/10.1086/321909. [36] M. D. Castellarnau et al., Deciphering the Interleukin 28B Variants That Better Predict Response to Pegylated Interferon-Α And Ribavirin Therapy in HCV/HIV-1 Coinfected Patients, Plos One, Vol. 7, No. 2, 2012, pp. e31016, https://doi.org/10.1371/journal.pone.0031016. [37] I. M. Jacobson et al., Telaprevir for Previously Untreated Chronic Hepatitis C Virus Infection, The New England Journal of Medicine, Vol. 364, No. 25, 2011, pp. 2405-2416, https://doi.org/10.1056/NEJMoa1012912. [38] V. Vadwai, B. R. Das, IL28B Genotyping: A Step Towards HCV-Personalized Therapy, International Journal of Gastroenterology Research and Practice, Vol. 2014, No. 2014, pp. 16, https://doi.org/10.5171/2014.212341. [39] F. About et al., Impact of IL28B, APOH and ITPA Polymorphisms on Efficacy and Safety pf TVR-Or BOC-Based Triple Therapy in Treatment-Experienced HCV-1 Patients with Compensated Cirrhosis from the ANRS CO20-CUPIC Study, PloS One, Vol. 10, No. 12, 2015, pp. e0145105, https://doi.org/10.1371/journal.pone.0145105. [40] G. Calisti et al., IL28B Genotype Predicts Response to Chronic Hepatitis C Triple Therapy with Telaprevir or Boceprevir in Treatment Naïve and Treatment-Experienced Patients Other Than Prior Partial-and Null-Responders, Springer Plus, Vol. 4, No. 1, 2015, pp. 1-9, https://doi.org/10.1186/s40064-015-1137-x. [41] S. Susser et al., Predictive Value of Interferon-Lambda Gene Polymorphisms for Treatment Response in Chronic Hepatitis C, Plos One, Vol. 9, No. 11, 2014, pp. e112592, https://doi.org/10.1371/journal.pone.0112592. [42] A. Tsubota et al., Impact of IL28B Polymorphisms on 24‐Week Telaprevir‐Based Combination Therapy for A Sian Chronic Hepatitis C Patients with Hepatitis C Virus Genotype 1b, Journal of Gastroenterology Hepatology, Vol. 29, No. 1, 2014, pp. 144-150, https://doi.org/10.1111/jgh.12402. [43] M. Manns et al., Simeprevir with Pegylated Interferon Alfa 2a or 2b Plus Ribavirin in Treatment-Naive Patients with Chronic Hepatitis C Virus Genotype 1 Infection (QUEST-2): A Randomised, Double-Blind, Placebo-Controlled Phase 3 Trial, The Lancet, Vol. 384, No. 9941, 2014, pp. 414-426, https://doi.org/10.1016/S0140-6736(14)60538-9. [44] M. Nakayama, H. Kobayashi, K. Fukushima, M. Ishido, Y. Komada, K. Yoshizawa, Predictive Factors for 24 Weeks Sustained Virologic Response (SVR24) and Viral Relapse in Patients Treated with Simeprevir Plus Peginterferon and Ribavirin, Hepatology International, Vol. 10, No. 1, 2016, pp. 158-168, https://doi.org 10.1007/s12072-015-9654-9. [45] F. Poordad et al., Factors that Predict Response of Patients with Hepatitis C Virus Infection to Boceprevir, Gastroenterology, Vol. 143, No. 3, 2012, pp. 608-618, https://doi.org/10.1053/j.gastro.2012.05.011. [46] C. Hézode et al., Daclatasvir Plus Peginterferon Alfa and Ribavirin for Treatment-Naive Chronic Hepatitis C Genotype 1 or 4 Infection: A Randomised Study, Gut, Vol. 64, No. 6, 2015, pp. 948-956, http://dx.doi.org/10.1136/gutjnl-2014-307498. [47] A Thompson et al., GS-5885 + GS-9451 + Peginterferon and Ribavrin (Pr) for Six or 12 Weeks Achieves A High SVR12 in Treatment Naïve Genotype 1 IL28B CC Patients, Journal of Hepatology, Vol. 58, No. Suppl 1, 2013, pp. S29, https://doi.org/10.1016/S0168-8278(13)60066-5. [48] S. Zeuzem et al., Pegylated Interferon-Lambda (Pegifn-Λ) Shows Superior Viral Response with Improved Safety and Tolerability Versus Pegifn-Α-2a In HCV Patients (G1/2/3/4): EMERGE Phase Iib Through Week 12, Journalof Hepatology, Vol. 54, No. Suppl 1, 2011, pp. S538, https://doi.org/10.1016/S0168-8278(11)61362-7. [49] S. Zeuzem et al., Faldaprevir and Deleobuvir for HCV Genotype 1 Infection, The New England Journal of Medicine, Vol. 369, No. 7, 2013, pp. 630-639, https://doi.org/10.1056/NEJMoa1213557. [50] T. R. O'Brien, S. Kottilil, J. J. Feld, T. R. Morgan, R. M. Pfeiffer, Race or Genetic Makeup for Hepatitis C Virus Treatment Decisions?, Hepatology, Vol. 65, No. 6, 2017, pp. 2124-2125, https://doi.org/10.1002/hep.29057. [51] R. M. Pfeiffer et al, Subgroup Differences in Response to 8 Weeks of Ledipasvir/Sofosbuvir for Chronic Hepatitis C, Open Forum Infectious Diseases, Vol. 1, No. 3, 2014, pp.1-4 ofu110, https://doi.org/10.1093/ofid/ofu110. [52] N. Akuta et al., Retreatment Efficacy and Predictors of Ledipasvir Plus Sofosbuvir to HCV Genotype 1 in Japan, Journal of Medical Virology, Vol. 89, No. 2, 2017, pp. 284-290, https://doi.org/10.1002/jmv.24617. [53] T. R. O’Brien, S. Kottilil, R. M. Pfeiffer, IFNL4 Genotype is Associated with Virologic Relapse After 8-Week Treatment with Sofosbuvir, Velpatasvir, and Voxilaprevir, Gastroenterology, Vol. 153, No. 6, 2017, pp. 1694-1695, https://doi.org/10.1053/j.gastro.2017.06.069. [54] A. J. Khan, V. A. Saraswat, P. Ranjan, D. Parmar, T. S. Negi, S. Mohindra, Polymorphism in Interferon Λ3/Interleukin‐28B Gene and Risk to Noncirrhotic Chronic Hepatitis C Genotype 3 Virus Infection and Its Effect on the Response to Combined Daclatasvir and Sofosbuvir Therapy, Journal of Medical Virology, Vol. 91, No. 4, 2019, pp. 659-667, https://doi.org/10.1002/jmv.25359. [55] A. Vasanthakumar et al., Reduced Itpase Activity and Favorable Il28b Genetic Variant Protect Against Ribavirin-Induced Anemia in Interferon-Free Regimens, Plos One, Vol. 13, No. 5, 2018, pp. e0198296, https://doi.org/10.1371/journal.pone.0198296. [56] H. Ahmed et al., Meta-Analysis of Grazoprevir Plus Elbasvir for Treatment of Hepatitis C Virus Genotype 1 Infection, Annals of Hepatology, Vol. 17, No. 1, 2018, pp. 18-32, https://doi.org/10.5604/01.3001.0010.7532 [57] J. J. Feld et al., Treatment of HCV with ABT-450/R–Ombitasvir and Dasabuvir with Ribavirin, New England Journal of Medicine, Vol. 370, No. 17, 2014, pp. 1594-1603, https://doi.org/10.1056/NEJMoa1315722. [58] S. Padmanabhan, Handbook of Pharmacogenomics and Stratified Medicine, Elsevier, London, 2014. [59] A. Osinusi, S. Naggie, The Role of IL28B Genotype Testing in The Era of Direct Acting Antiviral Agents, European Gastroenterology Hepatology Review, Vol. 1, No. 2, 2012, pp. 33-39. [60] Ministry of Health, Technical Guidelines on HBV Diagnosis and Treatment, Ministry of Health, Hanoi, 2019 (in Vietnamese). [61] Y. Yano et al., Factors Associated with the Decrease in Hepatitis B Surface Antigen Titers Following Interferon Therapy in Patients with Chronic Hepatitis B: Is Interferon and Adefovir Combination Therapy Effective?, Biomedical Reports, Vol. 7, No. 3, 2017, pp. 257-262, https://doi.org/10.3892/br.2017.944. [62] H. L. Y. Chan et al., A Randomized, Controlled Trial of Combination Therapy for Chronic Hepatitis B: Comparing Pegylated Interferon-Α2b and Lamivudine with Lamivudine Alone, Annals Of Internal Medicine, Vol. 142, No. 4, 2005, pp. 240-250, https://doi.org/10.7326/0003-4819-142-4-200502150-00006. [63] H. L. Janssen et al., Pegylated Interferon Alfa-2b Alone or in Combination with Lamivudine for Hbeag-Positive Chronic Hepatitis B: A Randomised Trial, The Lancet, Vol. 365, No. 9454, 2005, pp. 123-129, https://doi.org/10.1016/S0140-6736(05)17701-0. [64] G. K. Lau et al., Peginterferon Alfa-2a, Lamivudine, and The Combination for Hbeag-Positive Chronic Hepatitis B, New England Journal of Medicine, Vol. 352, No. 26, 2005, pp. 2682-2695, https://doi.org/10.1056/NEJMoa043470. [65] Z. Zhao et al., The Impact Of IFNL3 Genotype on Interferon Treatment Outcome in Patients Chronically Infected with Hepatitis B Virus: A Meta-Analysis, Microbial Pathogenesis, Vol. 134, 2019, pp. 103598, https://doi.org/10.1016/j.micpath.2019.103598. [66] M. Lindgren et al., Genetic Variation in IL 28B (IFNL 3) and Response to Interferon‐Alpha Treatment in Myeloproliferative Neoplasms, European Journal of Haematology, Vol. 100, No. 5, 2018, pp. 419-425, https://doi.org/10.1111/ejh.13034. [67] P. J. Campbell, A. R. Green, The Myeloproliferative Disorders, New England Journal of Medicine, Vol. 355, No. 23, 2006, pp. 2452-2466, https://doi.org/10.1056/NEJMra063728. [68] R. T. Silver, J. J. Kiladjian, H. C. Hasselbalch, Interferon and The Treatment of Polycythemia Vera, Essential Thrombocythemia and Myelofibrosis, Expert Rev Hematol, Vol. 6, No. 1, 2013, pp. 49-58, https://doi.org/10.1586/ehm.12.69. [69] R. T. Silver, K. Vandris, J. J. Goldman, Recombinant Interferon-Alpha May Retard Progressionof Early Primary Myelofibrosis: A Preliminary Report, Blood, Vol. 117, No. 24, 2011, pp. 6669-6672, https://doi.org/10.1182/blood-2010-11-320069. [70] M. Lindgren et al., A Retrospective Cohort Study of Interferon-Α Therapy in Myeloproliferative Neoplasms; Adverse Events, Thromboembolic Incidence and Causes of Termination of Therapy, Blood, Vol. 124, No. 21, 2014, pp. 1861, https://doi.org/10.1182/blood.V124.21.1861.1861. [71] P. H. Phiet et al., Rs12979860 and Rs8099917 Single Nucleotide Polymorphism of IL28B Gene in South Vietnam Patients Infected with Hepatitis C Virus, Journal of Hepatobiliary Vietnam, Vol. 21, 2012, pp. 9-16 (in Vietnamese). [72] P. T. T. Thuy et al., The Different Impacts of IL28B Genotype in Treatment Vietnamese Patients with Chronic Hepatitis C Genotype 1 and 6, Journal of Hepatobiliary Vietnam, Vol. 29, 2014, pp. 108-109 (in Vietnamese).